In vivo multifrequency magnetic resonance elastography of the human intervertebral disk - Streitberger, Kaspar-Josche; Diederichs, Gerd; Fehlner, Andreas; Hamm, Bernd; Braun, Juergen; Sack, Ingolf; Guo, Jing (Magnetic Resonance in Medicine, 2015)
Purpose To test in vivo magnetic resonance elastography (MRE) of the human intervertebral disk (IVD). Methods The feasibility of MRE in IVD was demonstrated in ex vivo bovine disks. Sixteen asymptomatic volunteers underwent multifrequency MRE of the lumbar spine (IVD L3/4 and L4/5, n = 32) using a posterior plate transducer connected to a loudspeaker and operated at five frequencies from 50 to 70 Hz. Full wave field data were acquired in 10 transverse slices of 2 × 2 × 2 mm3 resolution. High-resolution maps of magnitude |G| and phase angle φ of complex shear modulus G∗ were generated by multifrequency dual elasto visco (MDEV) inversion. Disk morphology was assessed by the Pfirrmann score (Pf). Results Morphological Pf was 1 in 25, 2 in 3, and 3 in 4 disks. |G| decreased with Pf by a Pearson's linear correlation coefficient of R = -0.592 (P = 0.0004), while φ remained unchanged. Group mean mechanical parameters for Pf = 1 to 3 were |G| = 6.51 ± 1.27, 5.29 ± 0.95, 4.03 ± 0.99 kPa, and φ = 1.190 ± 0.181, 1.170 ± 0.156, 1.088 ± 0.084 rad, respectively (p[Pf1-Pf3] < 0.001). The variability of mechanical parameters in one volunteer including diurnal changes was approximately 11%. Conclusion Multifrequency MRE with MDEV inversion allows measurement of in vivo mechanical properties of IVDs and may provide additional information in disc degeneration beyond standard morphological changes. Magn Reson Med 74:1380-1387, 2015.
CRIS-Team Scopus Importer:2022-08-03
Keywords: high resolution; intervertebral disks; magnetic resonance elastography; magnitude shear modulus; MRE; multifrequency dual elasto visco inversion; phase angle